Review: In the Wake of the Dhow: The Arabian Gulf and Oman - Smith, G. Rex (Journal of Semitic studies, 2004)
In the Wake of the Dhow: The Arabian Gulf and Oman Dionisius A. Agius , Ithaca Press, Reading 2002. xx + 253. 72 illustrations + 8 figs + 2 maps. Price: £35.00 . ISBN: 0-86372259-8